ПРОБЛЕМИ ЛІТЕРАТУРНОЇ ОСВІТИ В МЕТОДИЦІ СЛОВЕСНОСТІ СЕРЕДИНИ XIX – ПОЧАТКУ XX СТОЛІТТЯ - Новаківська, Людмила (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкрито проблеми літературної освіти в методиці словесності середини XIX – початку XX століття. У досліджуваний період вітчизняні методисти постійно ставили питання про кінцеву мету викладання словесності і, одночасно, структурували мотиви і шляхи її вивчення як у середній, так і у вищій школі. У практичних підходах вирішувалися, передусім, питання гармонізації об’єму давньої і сучасної літератури, усунення змістовної близькості гімназичного і університетського курсу словесності; прогностичні – виявляли значущість літератури як етико-естетичного, духовноформуючого предмета. В статье раскрыты проблемы литературного образования в методике словесности середины XIX – начала XX века. В исследуемый период отечественные методисты постоянно ставили вопрос о конечной цели преподавания словесности и, одновременно, структурировали мотивы и пути её изучения как в средней, так и в высшей школе. В практических подходах решались, прежде всего, вопросы гармонизации объема древней и современной литературы, устранение содержательной близости гимназического и университетского курса словесности; прогностические – показывали значимость литературы как этико-эстетического, духовноформирующего предмета. The article deals with the problem of literary education in the methods of the mid XIX – early XX century. In the second half of XIX – early XX century domestic methodists regularly asked questions about the ultimate goal of teaching literature and, simultaneously, structured motives and ways of studying both in high and in high school. Among the important tasks of teacher training literature would ensure continuity of literary education, which had both prognostic and applied nature. In practical approaches resolved, first of all, the question of harmonization of the volume of ancient and modern literature, elimination of substantial proximity gymnasium and university course literature; prognostic – showed the importance of literature as ethical and aesthetic, duhovnoformuyuchoho subject. It was found that the search for solution to the problem of succession of literary education in the mid XIX – early XX century was closely connected with solving three major methodological problems: overcoming hypertrophy ancient literature course; differentiation of literary history courses in high school and at the university; recognition of national literature spiritual basis of secondary and higher education.